The Speech Act Analysis of Cyberbullying on Instagram - Dewi, Munawati; Seli, Fenny Yutika (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
This study aimed to address two research questions concerning the frequency of illocution-related speech acts in connection with cyberbullying on Instagram. Data were collected from 100 comments on four Instagram accounts, and the analysis was done using the speech acts approach. The findings revealed that the speech act most frequently used in connection with cyberbullying on Instagram is the declarative type. Declarative speech acts are employed to create new names and terms, make official announcements, and follow ceremonial events. However, when used in the context of cyberbullying, these speech acts can have a detrimental impact on the victims. The study highlights the growing prevalence of cyberbullying on social media platforms like Instagram and its negative effects on victims. It also emphasizes the importance of understanding speech acts in the context of cyberbullying to improve communication and create a safer online environment.